Decision Affect Theory: Emotional Reactions to the Outcomes of Risky Options - Mellers, Barbara A; Schwartz, Alan; Ho, Katty; Ritov, Ilana (Psychological Science, 1997)
How do people feel about the outcomes of risky options? Results from two experiments demonstrate that the emotional reaction to a monetary outcome is not a simple function of the utility of that outcome Emotional responses also depend on probabilities and unobtained outcomes Unexpected outcomes have greater emotional impact than expected outcomes Furthermore any given outcome is less pleasant if an unobtained outcome is better We propose an account of emotional experiences associated with outcomes of decisions called decision affect theory It incorporates utilities expectations and counterfactual comparisons into hedonic responses Finally we show that choices between risky options can be described as the maximization of expected emotional experiences as predicted by decision affect theory That is people choose the risky option for which they expect to feel better on average